Energy-Saving Load Control of Induction Electric Motors for Drives of Working Machines to Reduce Thermal Wear - Al-Quraan, Tareq M. A.; Vovk, Oleksandr; Вовк, Олександр Юрійович; Halko, Serhii; Галько, Сергій Віталійович; Kvitka, Serhii; Квітка, Сергій Олексійович; Suprun, Olena; Супрун, Олена Миколаївна; Miroshnyk, Oleksandr; Мірошник, Олександр Олександрович; Nitsenko, Vitalii; et al. (Inventions, 2022)
The influence of reduced voltage on the service life of an induction motor is considered in this article. An algorithm for calculating the rate of thermal wear of induction motor insulation under reduced supply voltage depending on the load and the mechanical characteristics of the working machine has been developed. It determines the change in the rate of thermal wear under alternating external effects on the motor (supply voltage and load) and allows forecasting its service life under these conditions. The dependency graphs of the rate of insulation thermal wear on the motor load for various levels of supply voltage and various mechanical characteristics of working machines are provided in the work. It was determined that the rate of thermal wear of the induction motor insulation increases significantly when the voltage is reduced compared to its nominal value with nominal load on the motor. The authors propose to consider this fact for resource-saving control of the motor. The paper presents the results of experimental verification of the obtained rule for “Asynchronous Interelectro” (AI) series electric motors that confirm its accuracy. Based on the obtained correlation, the rule of voltage regulation in energy-saving operation mode has been derived. The proposed rule takes into account the thermal impact on the electric motor running in energy-saving mode and enables saving its resource, which, in turn, results in extending its service life. The research does not consider additional effects on the electric motor except the thermal one.
Keywords: induction motor; reduced voltage; working machine; motor load; insulation heating; thermal wear of insulation; extending service life; rule for voltage regulation